2011
DOI: 10.1038/onc.2011.98
|View full text |Cite
|
Sign up to set email alerts
|

Frequent homozygous deletion of the LKB1/STK11 gene in non-small cell lung cancer

Abstract: LKB1/STK11 is a tumor suppressor and a negative regulator of mammalian target of rapamycin signaling. It is inactivated in 30% of lung cancer cell lines but only 5–15% of primary lung adenocarcinomas. There is evidence that homozygous deletion (HD) of chromosome 19p at the LKB locus contributes to the inactivation of the gene in primary human lung cancers. Here, we used several complementary genetic approaches to assess the LKB1 locus in primary non-small cell lung cancers (NSCLCs). We first analyzed 124 NSCLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 40 publications
3
78
0
1
Order By: Relevance
“…It was shown that metformin, a biguanide antidiabetic drug and activator of the AMPK signaling, decreases the risk for cancer in diabetes patients (Evans et al, 2005). Furthermore, LKB1, a known upstream activator of AMPK signaling, has been described as tumor suppressor in lung cancer cells and mouse tumors (Ji et al, 2007;Gill et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that metformin, a biguanide antidiabetic drug and activator of the AMPK signaling, decreases the risk for cancer in diabetes patients (Evans et al, 2005). Furthermore, LKB1, a known upstream activator of AMPK signaling, has been described as tumor suppressor in lung cancer cells and mouse tumors (Ji et al, 2007;Gill et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Homozygous deletion or loss of heterozygosity (LOH) of chromosome 19p at the LKB1 locus occurred in 90% of the tested specimen in primary lung cancers. 50 The mutation is more frequent in lung cancers in smokers than neversmokers (P 0.007), and commonly occurs with K-Ras mutations (P 0.042) but infrequently with EGFR mutations (P 0.002). T790M (substitution of methionine for threonine at aa position 790) in tumours that progress on TKIs are more common in smokers and ex-smokers than in never-smokers.…”
Section: Cell Signalling Pathway Activation In Neversmokersmentioning
confidence: 99%
“…Several types of somatic mutations in LKB1 in sporadic cancers have been identified, including insertions, deletions (including large intragenic deletions), nonsense, frameshift, missense, and splice site alterations, and more infrequently hypermethylation of the promoter (28). Moreover, homozygous deletions of LKB1 have been frequently reported in NSCLC (29,30). Detection of genomic loss by DNA sequencing of clinical specimens is challenging because of the admixture with DNA from nontumor cells.…”
Section: Introductionmentioning
confidence: 99%